Social Change and the Idea of Urbanity Between Late Antiquity and Early Middle Ages - Maraković, Nikolina (Array, 2006)
The paper is an attempt at a multidisciplinary approach to the idea of the town in the period between Late Antiquity and Early middle ages. The town is perceived as a social space, defined by social dynamics, which is reflected in the urbanistic structure. The authors try to critically re-consider the accepted ideas such as "de-urbanization", "ruralization", "decline of urban culture", as well as the concepts of "continuity" and "discontinuity" in Late Antique Early medieval urbanism.